The Economics of Pain: A Conceptual Metaphor Analysis of Self-Commercialization in Ghalib’s Poetry - Maaz Jamal (Winaya Inspirasi Nusantara Foundation, 2026)
Mirza Ghalib’s canonical legacy rests almost exclusively on his Sufi mysticism and existential philosophy. Yet, the profound imprint of his lifelong financial precarity on his poetic framework remains critically under-examined. This study addresses this glaring lacuna in Urdu literary criticism by demonstrating how market rationality and mercantile metaphors fundamentally organize Ghalib’s ontology. Drawing on Lakoff and Johnson’s Cognitive Metaphor Theory, we conduct a qualitative content analysis of purposively selected verses from the Diwan-e-Ghalib, tracking specific economic lexical markers such as qarz (debt), sauda (trade/bargain), and daam (price). The analysis reveals that Ghalib constructs a